RANCANG BANGUN APLIKASI PRESENSI MENGGUNAKAN FINGERPRINT BERBASIS MOBILE DI PT. RAY PROPERTINDO - Firman Subhi; Jamaludin - (STIKOM CKI, 2019)
Attendance system at PT Ray Propertindo currently uses RFID card as an employee identification to conduct the presenting process. The company also has a policy of wage cuts in accordance with the accumulated time delays. But the problem is found that there is a tap RFID card by others so that employees who actually come late not recorded the delay. Another problem is, the existing system can notdirectly calculate the amount of wage deductions according to the needs of the company. Based on the problem, it required a fingerprint attendance system to avoid the process of attendance by others. In addition, a system that can read data from the fingerprint machine to calculate the appropriate wage deductions. Data collection methods used in this study using field studies in the form of interviews and observations as well as literature studies of journals related to the issues discussed. The SWOT method is used to determine the problem analysis. For the design method used UML as visual modeling. With the creation of this system, it can minimize the fraud on the attendance machine. Employees can see the performance of their attendance at any time. HRD staff can see directly how much the wage earned by each employee.